Análise geográfica da COVID-19: o caso da 8ª regional de saúde - Francisco Beltrão – Paraná - Cristino, Uilian Caponi (2024)
This study aims to analyze the occurrence of covid-19 by examining aspects of socio-spatial dissemination and demonstrating how Geography can aid in understanding the dynamics of outbreaks and epidemics. Furthermore, comprehending how the city of Francisco Beltrão was affected by the pandemic is another goal.The quantitative methodological procedure is used through bibliographical and documentary research and interviews as qualitative sources. Data were primarily taken from the Health Department’s platform, news from the city’s printed newspaper, and studies by authors engaged with the theme. The study sought to highlight key points and the effects of the pandemic at the national, state, and municipal levels, with a primary focus on the city of Francisco Beltrão. In this context, the spread of the virus, the release of funds to the city, and the measures taken by the public authorities during the pandemic were analyzed. Therefore, factors contributing to preventing the worsening of the pandemic were identified, including large-scale testing in the community on several occasions, providing more rigorous monitoring of the epidemiological situation, and the joint work of everyone involved. Afterward, with the vaccine's arrival, alongside increasing vaccine coverage, the progressive easing of Non Pharmacological Measures (NPM) began. During this period, there was a notable increase in cases; however, due to immunization, cases predominantly exhibited a mild nature, and the occurrence of new deaths became increasingly rare. The organizational issue and public policies must be meticulously reevaluated, considering that the covid 19 crisis went beyond the health area due to the incapacity of economic and human systems.